Effect of training intensity distribution on aerobic fitness variables in elite soccer players: A case study - Castagna, C.; Impellizzeri, F. M.; Chaouachi, A.; Bordon, C.; Manzi, V. (The Journal of Strength and Conditioning Research, 2011)
The aim of this article was to quantify the distribution of training intensities and its effect on aerobic fitness in professional elite soccer players. Fourteen professional soccer players were observed during the prechampionship training period (6 weeks). Treadmill running speed and heart rates (HRs) at 2 and 4 mmol/L blood-lactate concentrations were assessed pre and posttraining. Training intensities were categorized using 3 HR zones: low intensity (<HR 2 mmol/L), moderate intensity (between HR 2 and 4 mmol/L), and high intensity (>HR 4 mmol/L). Analysis of the 504 individual training sessions showed that 73 ± 2.5, 19 ± 2.8, and 8 ± 1.4% of the total training time was spent at low, moderate, and high intensity, respectively (p < 0.001). Speed at 2 and 4 mmol/L significantly improved posttraining (5 and 7%, respectively, p < 0.01). Training spent at high intensity was significantly related to relative speed improvements at 2 mmol/L (r = 0.84, p < 0.001;) and 4 mmol/L (r = 0.65, p = 0.001). Players spent almost two-thirds of their training time at low intensities. However, only the time spent at high intensity (>90% of maximal HR) was related to changes in aerobic fitness. These results support the usefulness of the quantification of aerobic training load using HR. Furthermore, it stresses the effectiveness of the high-intensity training in soccer.